The response of mesophyll conductance to short-term variation in CO2 in the C4 plants Setaria viridis and Zea mays. (21st February 2018) - Ubierna, Nerea; Gandin, Anthony; Cousins, Asaph B
Abstract : In two C4 species, mesophyll conductance increases with short-term exposure to decreasing p CO2 and limits photosynthetic capacity below ambient levels, whilst carbonic anhydrase imposes a further limitation only at very low p CO2 . Abstract: Mesophyll conductance ( g m ) limits rates of C3 photosynthesis but little is known about its role in C4 photosynthesis. If g m were to limit C4 photosynthesis, it would likely be at low CO2 concentrations ( p CO2 ). However, data on C4 - g m across ranges of p CO2 are scarce. We describe the response of C4 - g m to short-term variation in p CO2, at three temperatures in Setaria viridis, and at 25 °C in Zea mays . Additionally, we quantified the effect of finite g m calculations of leakiness (ϕ) and the potential limitations to photosynthesis imposed by stomata, mesophyll, and carbonic anhydrase (CA) across p CO2 . In both species, g m increased with decreasing p CO2 . Including a finite g m resulted in either no change or increased ϕ compared with values calculated with infinite g m depending on whether the observed 13 C discrimination was high ( Setaria ) or low ( Zea ). Post-transitional regulation of the maximal PEP carboxylation rate and PEP regeneration limitation could influence estimates of g m and ϕ. At p CO2 below ambient, the photosynthetic rate was limited by CO2 availability. In this case, the limitation imposed by the mesophyll was similar or slightly lower than stomata limitation. At very low p CO2, CA further constrained photosynthesis. High g m could increase CO2 assimilation at low p CO2 and improve photosynthetic efficiency under situations when CO2 is limited, such as drought.